Safety-related behavior as a social exchange: The role of perceived organizational support and leader–member exchange. - Hofmann, David A.; Morgeson, Frederick P. (Journal of Applied Psychology, 1999)
Researchers have been giving increased attention to the role larger organizational variables play in safety and accidents. Although generally neglected by this research, the nature of the exchange relationships between individuals, leaders, and the organization appears to have safety-related implications. The present research linked leader-member exchange (LMX) and perceived organizational support (POS) to safety communication, safety commitment, and accidents. Data were collected from 49 supervisor-group-leader dyads in a manufacturing facility. The results indicated that POS was significantly related to safety communication and that LMX was significantly related to safety communication, safety commitment, and accidents. Support was also found for a structural model linking POS and LMX to safety communication, safety commitment, and accidents. Implications of these findings for safety and social exchange research are outlined.